The works of Thomas M'Crie, D.D - M'Crie, Thomas (Thomas F. Torrance Collection., 1855)
Vol. I. Life of John Knox.--Vol. 2. Life of Andrew Melville.--Vol. III. The Reformation in Italy. The Reformation in Spain.--Vol. IV. Review of "Tales of my landlord". On the unity of the church: and sermons.